RITUAL KOMUNIKASI DALAM UPACARA ADAT ERAU SEBAGAI MODAL SOSIAL MASYARAKAT TRADISIONAL KUTAI KARTANEGARA - Herman, Azizah; Arisa, Rio (Journal of Sustainable Transformation, 2025)
The Erau ceremony, a tradition inherited from the Kutai Kartanegara Ing Martadipura Sultanate, is still preserved today as a form of respect for ancestors and an expression of gratitude to God Almighty. It is not only a ceremonial activity but also carries deep meaning in the communication among humans, nature, and spiritual forces. This research aimed to understand how communication rituals in Erau traditional ceremonies act as social capital in the traditional Kutai Kartanegara community. The method used was library research, involving the review of relevant literature, scientific journals, books, and electronic sources on cultural communication, traditional rituals, and social capital. Data were analyzed descriptively and qualitatively to reveal symbolic, social, and spiritual values ​​in the implementation of the Erau ceremony. The results showed Erau traditional ceremonies containing four main forms of communication rituals, namely: (1) symbolic communication, which is reflected in the use of symbols such as water and dragons as symbols of purification and balance; (2) spiritual communication, in the form of prayers and offerings to God and respect for ancestors; (3) social communication, which is seen through cooperation, mutual assistance and solidarity between citizens; and (4) cultural communication, through passing on values ​​and norms to the younger generation. These Erau rituals as social capital strengthen social networks, collective norms, and shared beliefs among the Kutai Kartanegara community. In addition, it plays an important role in maintaining social cohesion, strengthening local cultural identity, and upholding traditional values amid the currents of modernization and globalization. Thus, the Erau traditional ceremony is not just a cultural heritage but also an instrument of social communication that strengthens the sustainability of the traditional Kutai Kartanegara community's way of life.